Dabt Mushaf Uthmani: Perkembangan, Permasalahan dan Kaitannya dengan Pembangunan Sosial di Malaysia - Ismail, Daud; Hj. Ab Rahman, Asyraf; Wan Ahmad, Wan Ibrahim; Adam, Fadzli (Jurnal Usuluddin, 2004)
Dabt is a method used in Mushaf Uthmani to identify various forms of simbols related to the reading of the Quran. It is also considered as complimentary to the rasm (orthography) also referred to as al-rasm al-Uthmani. Efforts towards utilizing this methods in the reading of the Quran began since there were an increase in numbers of those converted into Islam particularly amongst the Ajam (non-Arabs). As a result a new approach was employed to preserve the originality of the Quran as well as enabled Muslims of various background to read correctly the text. In the contexts of the current Muslim scenario, a proper understanding of the writing methods of the Quran and its simbols are necessary since any ambiguity over the simbols would prevent Muslim from reading the Quran correctly. The Government of Saudi Arabia for instance, in its efforts to increase the use of Mushaf Uthmani, has established the Quranic Publishing Complex, Malik Fahd Publishing also known as Mujamma al-Malik Fahd li Tabaah al-Mushaf al-Sharif. As a Muslim country, Malaysia has also taken several stages towards the preservation of the Mushaf Uthmani. This paper therefore, tends to analyse the importance of dabt Mushaf Uthmani besides discussing arising issues and problems related to the preservation of the Mushaf Uthmani and the Quran in particular.